Study on sampling design for monitoring cultivated land quality at a county scale (Journal of agricultural resources and environment, 2020)
为准确掌握耕地质量等别空间分布特征，提高县域耕地质量监测效率，完善其监测体系，本研究以广州市从化区为例，基于耕地质量监测成果以及土壤、环境因子等数据，通过空间统计学、空间叠加等方法对县域耕地质量等别监测分区布点进行研究。结果表明，考虑土壤、地貌、土地利用水平、土地经济效益以及耕地质量渐变类型等因素，从化区共划分为26个耕地质量监测区。依据空间分层抽样原理，结合研究区内国家标准样地、沟渠、道路、村庄、基本农田等因素在空间上对监测样点进行调整，最终确定了111个监测样点。经统计检验表明，监测样点在总体耕地分等单元中具有较高的代表性。以此建立的县域耕地质量监测体系可为自然资源部门的耕地质量监测监管提供技术支持。 In order to accurately grasp the spatial distribution characteristics of cultivated land quality grades, improve the efficiency of county cultivated land quality monitoring, and complete its monitoring system, in this study, Conghua District in Guangzhou City had been taken as an example, based on cultivated land quality monitoring results, soil, environmental factors and other data, studying sampling design by monitoring cultivated land quality at a county scale through spatial statistics and spatial superposition. By considering factors such as soil, landforms, land use level, land economic benefits, and gradual types of cultivated land quality, Conghua District was divided into 26 cultivated land quality